1998
DOI: 10.1046/j.1365-2427.1998.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Ficusand Eucalyptusleaves in an organically polluted river in India: fungal diversity and ecological functions

Abstract: 1. At two organically polluted sites in the River Nethravathi, banyan and eucalypt leaves were colonized by one or two species of aquatic hyphomycetes. A total of three or four species were identified at the two sites in samples of water and naturally occurring leaves. 2. Spore production from stream‐exposed leaves by aquatic hyphomycetes was lower by a factor of up to 1 million compared with an earlier study in geographically close but unpolluted streams. 3. Exponential decay rates and loss rates of phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 37 publications
6
31
2
Order By: Relevance
“…The species richness of aquatic hyphomycetes associated with alder leaves at studied sites (20 to 25 species) was similar to that found in a nonpolluted stream from central Portugal (5) and slightly higher than that observed during the previous autumn in the Ave River (37). Although aquatic hyphomycetes have been associated with clean and well-aerated waters (4) and low diversity has been reported in an organically polluted stream (3 or 4 species [38]), they appear to be rather well represented in streams with either heavy-metal (13 or 14 species [42]) or organic and inorganic (18 to 23 species [37]) pollution. CA ordination of sampling sites and dates on the basis of aquatic hyphomycete assemblages on leaves separated reference (L1 and L2) from polluted (L6 and L7) sites, suggesting that shifts in the structure of fungal communities were associated with changes in the water chemistry.…”
Section: Discussionsupporting
confidence: 77%
“…The species richness of aquatic hyphomycetes associated with alder leaves at studied sites (20 to 25 species) was similar to that found in a nonpolluted stream from central Portugal (5) and slightly higher than that observed during the previous autumn in the Ave River (37). Although aquatic hyphomycetes have been associated with clean and well-aerated waters (4) and low diversity has been reported in an organically polluted stream (3 or 4 species [38]), they appear to be rather well represented in streams with either heavy-metal (13 or 14 species [42]) or organic and inorganic (18 to 23 species [37]) pollution. CA ordination of sampling sites and dates on the basis of aquatic hyphomycete assemblages on leaves separated reference (L1 and L2) from polluted (L6 and L7) sites, suggesting that shifts in the structure of fungal communities were associated with changes in the water chemistry.…”
Section: Discussionsupporting
confidence: 77%
“…Effects of changing autochthonous mixed oak forest litter by eucalyptus litter could be expected at the community level, since Raviraja et al (1998) and Yeates & Barmuta (1999) found that consumption and growth rates are reduced in eucalyptus-fed macroinvertebrates irrespective of the functional feeding group. Similarly, Abelho & Graça (1996) found less macroinvertebrates in reaches below eucalyptus plantations than in reaches under autochthonous deciduous forests.…”
Section: Influence Of Eucalyptus Litter Addition On Stream Invertebratesmentioning
confidence: 99%
“…Usually species richness will be higher in mixed leaf litter (e.g. Sridhar & Kaveriappa 1988, Chandrashekar et al 1990Sridhar et al 1992) than immersed single leaf litter (Raviraja et al 1996(Raviraja et al , 1998b. However, there are some exceptions, for instance: banyan (Ficus benghalensis) leaves was a preferred substrate compared to other leaf litter (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies are available on the leaf chemistry (Raviraja et al 1996(Raviraja et al , 1998b) and leaf enzymes (Raviraja et al 1998b) linked with the activities of aquatic hyphomycetes in the Western Ghats. As seen in earlier studies, the present study also reveals increase in leaf nitrogen (corroborates studies by Bärlocher 1985, Webster & Benfield 1986 and decrease in leaf phosphorus and leaf phenolics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation